El debido proceso y la cadena de custodia frente a las pruebas judiciales presentadas por el auditor forense (2017)
This paper has as main objective describe the process to be followed in the chain of custody as is mentioned in the law 906 of 2004 (Colombian Republic congress, 2004), specifically in topics related to forensic audit, the mentioned before taking into account that all audit processes must to be adjust to the International Audit Standards (IAS), stated in the decree 2420 of December of 2015 (Presidency of the Republic of Colombia, 2015), which guarantee efficiency and effectiveness in such process. In the same way, within the execution of the forensic audit must be take into account the extend and sufficient expert evidence and the actual scientist grade of acceptation, as well as the relevance who has the due process in the custody chain, which will allow get a high confidence level in a judicial process.